Who are the nonusers of sunscreen, and what are their reasons?: Development of a new item set - Diehl, Katharina; Schneider, Sven; Seuffert, Svenja; Greinert, Rüdiger; Görig, Tatiana (Journal of cancer education, 2021)
Sunscreen use is an important aspect of sun protective behavior. Previous studies revealed deficits in sunscreen use. Our aim was to quantify sunscreen use in a nationwide representative study in Germany as well as to develop and test an item battery on reasons for none use of sunscreen. We analyzed data of the National Cancer Aid Monitoring (NCAM; wave 4; n = 3000, aged 14-45). To describe those who only use sunscreen rarely or never, we used chi2 statistics and logistic regression analysis. In addition, we utilized a newly developed item battery on barriers to sunscreen use. Here, we used Cronbach’s alpha to investigate reliability. In total, 20.7% reported using sunscreen rarely or never. Infrequent or none use of sunscreen was associated with male sex, immigrant background, none or rare sunbathing in summer, and current or past use of sunbeds. Participants with higher skin cancer risk (e.g., pale skin) were less likely to use sunscreen infrequently or never. The major reasons for not using sunscreen were inconvenience and no perceived need for applying sunscreen. Overall, internal consistency of the item battery on potential barriers to sunscreen use was very good (Cronbach’s alpha = 0.865). We found deficits in sunscreen use especially in sunbed users, men, and individuals with immigrant background. Our results give important implications for future prevention and health promotion campaigns on sunscreen use.